Kynurenine pathway metabolism following prenatal KMO inhibition and in Mecp2+/− mice, using liquid chromatography-tandem mass spectrometry. (November 2016) - Forrest, Caroline M.; Kennedy, Peter G.E.; Rodgers, Jean; Dalton, R. Neil; Turner, Charles; Darlington, L. Gail; Cobb, Stuart R.; Stone, Trevor W.
Abstract: To quantify the full range of tryptophan metabolites along the kynurenine pathway, a liquid chromatography – tandem mass spectrometry method was developed and used to analyse brain extracts of rodents treated with the kynurenine-3-mono-oxygenase (KMO) inhibitor Ro61-8048 during pregnancy. There were significant increases in the levels of kynurenine, kynurenic acid, anthranilic acid and 3-hydroxy-kynurenine (3-HK) in the maternal brain after 5 h but not 24 h, while the embryos exhibited high levels of kynurenine, kynurenic acid and anthranilic acid after 5 h which were maintained at 24 h post-treatment. At 24 h there was also a strong trend to an increase in quinolinic acid levels (P = 0.055). No significant changes were observed in any of the other kynurenine metabolites. The results confirm the marked increase in the accumulation of some neuroactive kynurenines when KMO is inhibited, and re-emphasise the potential importance of changes in anthranilic acid. The prolonged duration of metabolite accumulation in the embryo brains indicates a trapping of compounds within the embryonic CNS independently of maternal levels. When brains were examined from young mice heterozygous for the meCP2 gene – a potential model for Rett syndrome - no differences were noted from control mice, suggesting that the proposed roles for kynurenines in autism spectrum disorder are not relevant to Rett syndrome, supporting its recognition as a distinct, independent, condition. Highlights: Pregnant rats were treated with an inhibitor of kynurenine-3-monoxygenase. Levels of several kynurenine metabolites increased in the maternal and foetal brains. The maternal changes at 5 h disappeared by 24 h, but were maintained in embryos. No changes were noted in the brains of Mecp2 +/− mice. KMO inhibition but not Mecp2 +/− suppression alters kynurenine metabolism.